A collaboration approach for cloud factories based on Kuhn-Munkras algorithm - Huo, Yunliang; Xiong, Ji; Guo, Zhixing; Wenjun, Xiao; Lei, Liang (International journal of computer integrated manufacturing, 2022)
Cloud manufacturing (CMfg) is a network-based and service-oriented resource-sharing manufacturing paradigm, where resources from different factories are encapsulated as services that can be jointly employed to complete manufacturing tasks. To provide an efficient collaboration strategy among the factories in CMfg, in this work, a universal framework was proposed to describe manufacturing resources under the cloud environment, in which both equipment and factory levels were considered. Moreover, a collaboration model among cloud factories was presented from the perspective of the bipartite graph. Specifically, the surplus and demands of resources were mapped to vertex vectors of the bipartite graph, respectively. Collaboration expectations of each factory, QoS (quality of service) and supply-demand balance of manufacturing capacity were evaluated as the matching degree. Furthermore, the Kuhn-Munkras(KM) algorithm, which is good at bipartite graph matching, was adopted to solve the proposed model. Finally, results from simulation confirmed that the proposed method is feasible and advanced, in comparison with the current related methods.